2001
DOI: 10.1530/eje.0.1450119
|View full text |Cite
|
Sign up to set email alerts
|

B-cell autoepitopes on the acetylcholinesterase-homologous region of human thyroglobulin: association with Graves' disease and thyroid eye disease

Abstract: Objective: Thyroglobulin (Tg) is a large autoantigen involved in autoimmune thyroid diseases. Tg epitopes have, so far, been identi®ed within large peptides. In the present study, we used small synthetic peptides to ®nely map serological epitopes on the highly immunogenic C-terminal region of Tg. Homology of this region to acetylcholinesterase (AChE) has been implicated in the pathogenesis of thyroid eye disease (TED) through cross-reactive antibodies. Methods: We tested total IgG puri®ed from four pilot Grave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…The majority of the determinants encompassed within these sites are recognized by CD4 þ and mouse MHC class II-restricted T cells; one was recognized by an MHC class I-restricted, cytotoxic T-cell (CTL) hybridoma (18); recently, four hTg peptides were described eliciting EAT in HLA-DR3-transgenic mice (21,26). Within the last group, of note are hTg peptides p2079, which elicits considerable EAT both directly and by adoptive transfer assays (21), and p2340 (23,26), which was originally shown to be a target of Tg-reactive Abs in patients with Graves' disease (27). To a large extent, these findings reflected the bias of the screening approach; for example, since susceptibility to EAT is A k controlled, computerized algorithms were used to search for A k -binding, pathogenic Tg peptides.…”
Section: Noniodinated But Pathogenic Tg Peptidesmentioning
confidence: 99%
“…The majority of the determinants encompassed within these sites are recognized by CD4 þ and mouse MHC class II-restricted T cells; one was recognized by an MHC class I-restricted, cytotoxic T-cell (CTL) hybridoma (18); recently, four hTg peptides were described eliciting EAT in HLA-DR3-transgenic mice (21,26). Within the last group, of note are hTg peptides p2079, which elicits considerable EAT both directly and by adoptive transfer assays (21), and p2340 (23,26), which was originally shown to be a target of Tg-reactive Abs in patients with Graves' disease (27). To a large extent, these findings reflected the bias of the screening approach; for example, since susceptibility to EAT is A k controlled, computerized algorithms were used to search for A k -binding, pathogenic Tg peptides.…”
Section: Noniodinated But Pathogenic Tg Peptidesmentioning
confidence: 99%
“…The hTg peptide PYEFSRKVPT FATPWPDFVP (aa 2652e2671, p2652) was synthesized by Genosys Biotechnologies (Cambridge, UK) and used as control. Its properties are previously described [9]. Both peptides were used in all experiments at O80% purity as determined by analytical HPLC and mass spectral analyses.…”
Section: Antigensmentioning
confidence: 99%
“…Eight of them have been identified in mouse Tg (mTg), three in human Tg (hTg) and two, sharing identical amino acid sequence between mTg and hTg (contain the hormonogenic sites of Tg). In this study, we focused on hTg 20-mer peptide p2340 (aa 2340e2359) which was initially shown to be a target of Tg-reactive autoantibodies occurring in Tg/acetylcholinesterase reactive sera from patients with Graves' disease [9]. Furthermore, p2340 was found to be able to elicit E k -restricted thyroiditis in AKR/J (H-2 k ) mice.…”
Section: Introductionmentioning
confidence: 99%
“…[6] This site is known to also contain an epitope recognized by autoantibodies in patients with Graves' disease. [13] Lastly, the 14 mer (2730 -2743) has been reported to induce EAT in CBA mice only after adoptive transfer of LNC that were primed in vivo with mTg and boosted in vitro with the peptide. [14] Direct challenge of mice with this peptide or adoptive transfer of peptide-specific spleen cells did not induce thyroid pathology.…”
Section: Eat-causing Peptides In Mtgmentioning
confidence: 99%